Mapping the Natural and Cultural Tourism Potential of Seputih Village, Mayang District: A Pilot Project for Sustainable Tourism Villages in Jember Regency - NH, Uystka Hikmatul Kamiliyah; Milawaty, Milawaty; Diartika, Firda; Rizka, Hablana; Utami, Lely Dian; Habibie, Aldino Candra (P3M Politeknik Negeri Jember, 2025)
The Regional Government of Jember is currently intensifying efforts to develop the tourism sector in Jember Regency. This development is focused on evolving tourism potential that prioritizes local wisdom and cultural preservation. Seputih Village, located in Mayang District, Jember Regency, is one of the villages targeted by the government to become a sustainable tourism village in Jember Regency for its natural and cultural potential. Thus, it is necessary to assess this potential through a proper mapping to identify the natural and cultural attractions that can be developed. Hence, this research is focused on assessing and mapping the potential of natural and cultural tourism in Seputih Village as a pilot project for Sustainable Tourism Villages in Jember Regency. The research method used is descriptive qualitative with data collection techniques in the form of field observations, in-depth interviews, thematic mapping techniques, documentation, and literature studies. The research results indicate that Seputih Village has numerous natural and cultural potential that can be assessed and developed as tourism attractions. Some of the natural tourism potential include Goa Landak Waterfall, Wringin Lawang Waterfall, Mrawan Dam, and the Alas Perhutani Café Rest Area. Furthermore, cultural tourism potential includes Sarcophagus site, Ludruk Bintang Jaya, and Campursari Sinar Jaya. These natural and cultural tourism potential were mapped as an initial step to evolve Seputih Village as a recognized tourism village. Ultimately, this mapping of tourism potentials is expected to assist Seputih Village to develop as a sustainable tourism village in Jember Regency.